Swimming Learning Method Early Childhood - M. Imran Hasanuddin Imran; Muhammad Akbar Syafruddin; Retno Farhana Nurulita Retno; Muhammad Qasash Hasyim (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
The purpose of this research is to learn new things and make discoveries. The second is to show or validate the accuracy of previously held beliefs, and the third is to ascertain how the model of early childhood swimming develops. This research was conducted in a library. The research data is secondary. The documentation method of data collection is used in this research. Article content analysis is a technique used for analysis. When research articles meet the criteria, they are submitted, and a journal summary is prepared, which includes the name of the researcher, year of publication of the journal, study design, objectives, sample, tools (such as measurement instruments), and research summary. findings. There are ten publications that discuss swimming learning models in early childhood; all of these publications are national journals. To find it, use the keyword "swimming learning models" in the Google Scholar search box. The articles were then critically assessed to determine the similarities and differences between them. Of the 10 journals, 5 discussed topics such as gross motor skills, game modification, and capacities rather than explicitly examining swimming play. Identification of early childhood swimming learning methods by explaining efficient methods from several related studies so that they can be used as a reference for early childhood swimming learning is one of the important things obtained from various journals. Second, the Swimming Sports Learning Model for Young Children can Grow Interest and Prevent Boredom. Third, the learning process is more fun and interactive and has a good impact on gross motor skills and cognitive capacities in early childhood.